Does Access to Finance Reduce Poverty? Evidence from Katsina State - Aliero, Haruna Mohammed; Ibrahim, Saifullahi Sani (Richtmann Publishing, 2012)
Enhancing access to formal financial services especially credit to the rural populace has been identified as a means ofreducing poverty in developing countries. This paper investigates whether access to financial services reduces poverty in Nigeriafocusing specially on rural areas. A cross-sectional primary data was generated using a structured questionnaire administeredon randomly selected respondents from rural areas of Katsina state. The study used multinomial logit model in examining therelationship, and the study found a negative relationship between poverty level and access to financial services. The studyconcludes that promoting access to formal financial services increases the level of income of the rural dwellers and thus aretarding effect on the level of poverty in the rural areas.